The Centralize Data by Utilizing CMIS to Assist Church Leaders in Making Strategic Plans (Case Study: XYZ Church) - Setiawan, Putri Sanggabuana (Bina Nusantara University, 2024)
Congregations are social entities that require a sense of community to function effectively. One of the most prominent locations for community engagement is the church. The diverse needs of congregants drive their attendance at church, including worship, social interaction, and spiritual growth. To fulfill these needs, churches offer a wide range of programs. To effectively address these needs, churches must have a clear understanding of the requirements of their congregants. A church management information system (CMIS) provides insight into the congregation's needs, enabling church leaders to comprehend their congregants' requirements and develop a strategic plan. The XYZ Church CMIS and data governance were developed based on a comprehensive literature review and input from IT professionals engaged in group discussions. This research's objective was to develop a CMIS to collect and manage data on the congregation and church. The insights from the CMIS have enabled church leaders to adjust event schedules. Prior to the implementation of the CMIS, the average attendance at events was below 20%. A review of the CMIS data over a 12-month period, in conjunction with the insights gained from group discussions with church leaders, revealed that event attendance had risen to above 70%. The church management information system has proven to be an effective tool for church leaders to create strategic plans for event scheduling, resulting in increased event attendance. In future research, it would be beneficial to consider not only enhancing event attendance but also increasing the number of congregants